Inovasi Pembelajaran Fisika melalui Game Wordwall pada Materi Gerak Lurus - Maspiah, Maspiah (Jurnal Pendidikan Madrasah, 2025)
This study aims to develop a physics educational game using Wordwall for the topic of linear motion and to assess its feasibility, practicality, and effectiveness. The research employed a Research and Development (R&D) approach with the ADDIE development model. The participants consisted of 28 eleventh-grade students at MAN 2 Tuban. Data was collected through expert validation (media and content), student response questionnaires, and learning achievement tests (pretest and posttest). Validation results indicated a high level of feasibility, with average scores of 85% from media experts and 84.6% from content experts. The practicality level, based on student responses, reached 92.86% (categorized as highly practical). The effectiveness of the media was demonstrated by an increase in the average score from 20.18 (pretest) to 36.39 (posttest), with mastery learning improving from 89.29% to 100%. These findings suggest that the Wordwall-based educational game is feasible, practical, and effective in enhancing students’ learning outcomes on linear motion.